Seakeeping criteria of a moored and articulated multibody floating platform in head seas - Jiang, Changqing; el Moctar, Ould; Zhang, Guiyong (Frontiers in Marine Science, 2023)
Within the Space@Sea project, a multi-use floating concept was proposed by following the analogy of standardization to enlarge a floating platform using a multitude of smaller structures. An operability analysis must be performed to identify its seakeeping criteria and how the criteria limit its functionality. A two-step strategy is proposed to calculate the responses of the target floating concept in head waves, where nonlinearities of the mooring lines and mechanical joints are taken into account. The weakly nonlinear time-domain procedure relies on a diffraction-radiation model in the frequency domain. The motions of floating bodies are solved in the time domain, in which nonlinear Froude-Krylov and hydrostatic forces are estimated under instantaneous incident wave surface. Multibody interactions are resolved under consideration of catenary mooring lines and hinged joints. Wave-induced motions and loads are expressed in terms of transfer function for determining the limiting criteria, including the translational and rotational motions velocities and accelerations; relative motions, velocities and accelerations between module floaters; mooring tensions; as well as hinge forces. Assessments are carried out for various sea conditions against the prescribed values, for the chosen criteria, to address safety issues due to sever platform responses. Different operational requirements for trained workers and untrained passengers of motions and accelerations are taken into consideration. Results show that rotational motions have a significant influence on the platform’s seakeeping performance. Nevertheless, the root mean square (RMS) value of vertical acceleration dominates the comfort of persons onboard, defining the final limiting criterion of the entire platform.